Suitability of varieties, requirement of plant population and response of summer groundnut (Arachis hypogaea) to levels of gypsum and phosphorus in rice (Oryza sativa) fallows - RAO, K S; MOORTHY, B T S (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during the summer seasons of 1991 and 1992 on alluvial sandy-loam soils of Cuttack (coastal region of Orissa) to identify a suitable high-yielding variety of groundnut (Arachis hypogaea L.) in rice (Oryza sativa L.) fallows and suitable technology for higher productivity of the crop. The promising varieties were ’R 8808’, ’ICGS 11’ and ’DRG 12’ with mean yields of 3.55, 3.33 and 3.26 tonnes/ha respectively. The crop sown at the spacings of 40 cm X 10 cm (250 000 plants/ha), 30 cm X 10 cm(333Â 000 plants/ha) and 20 cm X 15 cm (333 000 plants/ha) gave significantly higher yield (2.60, 2.79 and 2.82 tonnes/ha respectively) than that grown under the spacings of 20 cm X 10 cm (500 000 plants/ha). 30 cm X 15 cm (222 000 plarus/ha) and 40 cm X 15 cm (166 666 plants/ha). The crop responded to gypsum @ 500 kg/ha applied 30 days after germination, and to P @17.46kg/ha applied at sowing.